2019
DOI: 10.1038/s41598-019-41039-x
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol inhibits eukaryotic Ser/Thr phosphatase and infection-specific cell differentiation in the rice blast fungus

Abstract: Chloramphenicol (Cm) is a broad-spectrum classic antibiotic active against prokaryotic organisms. However, Cm has severe side effects in eukaryotes of which the cause remains unknown. The plant pathogenic fungus Magnaporthe oryzae , which causes rice blast, forms an appressorium to infect the host cell via single-cell differentiation. Chloramphenicol specifically inhibits appressorium formation, which indicates that Cm has a novel molecular target (or targets) in the rice blast fungus. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…However, cDNA sequencing showed that only the alleles without the nonsense mutation were being amplified, possibly due to the targeting of nonsense alleles to nonsense-mediated mRNA decay. Chloramphenicol may act through a mechanism other than stop codon read-through [ 275 ] Chloramphenicol n.a In vitro molecular. Read-through level of cspC UGA in E. coli Chloramphenicol increased read-through [ 276 ] Oxazolidinones Linezolid n.a In vitro molecular , lacZ ± UAG or UGA Induction of read-through [ 273 ] Linezolid, Rχ-01 n.a In vitro molecular , lacZ ± UAG or UGA Linezolid induced read-through 5-times less efficient than the investigational oxazolidin Rχ-01 [ 277 ] Tetracyclines Tetracycline n.a In vitro molecular.…”
Section: Drug Class Specific Non-antimicrobial Activities Of Antibiotmentioning
confidence: 99%
See 3 more Smart Citations
“…However, cDNA sequencing showed that only the alleles without the nonsense mutation were being amplified, possibly due to the targeting of nonsense alleles to nonsense-mediated mRNA decay. Chloramphenicol may act through a mechanism other than stop codon read-through [ 275 ] Chloramphenicol n.a In vitro molecular. Read-through level of cspC UGA in E. coli Chloramphenicol increased read-through [ 276 ] Oxazolidinones Linezolid n.a In vitro molecular , lacZ ± UAG or UGA Induction of read-through [ 273 ] Linezolid, Rχ-01 n.a In vitro molecular , lacZ ± UAG or UGA Linezolid induced read-through 5-times less efficient than the investigational oxazolidin Rχ-01 [ 277 ] Tetracyclines Tetracycline n.a In vitro molecular.…”
Section: Drug Class Specific Non-antimicrobial Activities Of Antibiotmentioning
confidence: 99%
“…Read-through level of cspC UGA in E. coli Chloramphenicol increased read-through [ 276 ] Oxazolidinones Linezolid n.a In vitro molecular , lacZ ± UAG or UGA Induction of read-through [ 273 ] Linezolid, Rχ-01 n.a In vitro molecular , lacZ ± UAG or UGA Linezolid induced read-through 5-times less efficient than the investigational oxazolidin Rχ-01 [ 277 ] Tetracyclines Tetracycline n.a In vitro molecular. Read-through level of cspC UGA in E. coli Tetracycline increased read-through [ 275 ] Doxycycline Breast cancer In vitro cellular, murine breast cancer EMT6 cells. The genetic code of the amino acid selenocysteine is UGA Most selenoproteins are oxidoreductases involved in housekeeping processes and stressresponse.…”
Section: Drug Class Specific Non-antimicrobial Activities Of Antibiotmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that Scp1 may represent a potential drug target and Scp1-specific inhibitors may represent valuable therapeutics for preventing the spreading of particular tumors. To date, some studies have reported specific inhibitors for FCP/SCP-type PSPs, including for Scp1 [30,31]. It is reported that rabeprazole, which is a drug for gastroesophageal reflux disease, can function as a specific inhibitor for Scp phosphatases including Scp1, but it did not show the inhibitory activity against other FCP/SCP type phosphatase, Fcp1 and Dullard, or bacteriophage λ Ser/Thr phosphatases [30,32].…”
Section: Introductionmentioning
confidence: 99%